State regulation of investment in agriculture - Lysa, O.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Azhazha, M.; Venger, O.; Sergiienko, T. (My University, 2022)
An important task of state regulation of investment in the agricultural sector of the economy is to attract investors who are able to increase the efficiency of the functioning of agricultural enterprises. The success of the functioning of this enterprise depends on how quickly an agricultural enterprise is able to adapt to changes in the external environment. This is achievable under the condition of the most optimal use of the enterprise's resource potential. Small agricultural enterprises are usually deprived of the possibility of using highly productive innovative agricultural technologies in their activities due to their high cost. Farm enterprises are also experiencing difficulties with insurance and attracting bank loans. In the competition with large agricultural enterprises, small farms survive mainly thanks to state subsidies. Large agricultural holdings are more financially stable, their economic activities are more diversified compared to farms. At large agricultural enterprises, labor productivity is higher and the cost of production is lower. The main task of the state for ensuring food security is to facilitate the process of consolidation of agricultural enterprises. The liquidation of small farming enterprises is an objective process that results from free market competition. The consolidation of agricultural enterprises will allow more efficient use of agricultural land in agricultural production.
Keywords: investment; economy; investors